2013
DOI: 10.1186/1748-5908-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a knowledge application program for anxiety and depression in community-based primary mental health care: a multiple case study research protocol

Abstract: Background: Anxiety and depressive disorders are increasingly recognized as a health care policy priority. Reducing the treatment gap for common mental disorders requires strengthening the quality of primary mental health care. We developed a knowledge application program designed to improve the organization and delivery of care for anxiety and depression in community-based primary mental health care teams in Quebec, Canada. The principal objectives of the study are: to implement and evaluate this evidence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The results of this study are in line with several studies stating that there is a significant relationship between knowledge and situation (29,37). The above is closely related to public awareness about hypertension if individual knowledge about hypertension will motivate patients to participate in modifying lifestyles such as losing weight, reducing alcohol consumption, regular exercise and increased consumption of fruits and vegetables.…”
Section: Relationship Knowledge and Anxiety Respondents Hypertensionsupporting
confidence: 89%
“…The results of this study are in line with several studies stating that there is a significant relationship between knowledge and situation (29,37). The above is closely related to public awareness about hypertension if individual knowledge about hypertension will motivate patients to participate in modifying lifestyles such as losing weight, reducing alcohol consumption, regular exercise and increased consumption of fruits and vegetables.…”
Section: Relationship Knowledge and Anxiety Respondents Hypertensionsupporting
confidence: 89%
“…A consulting psychiatrist was available to assist family physicians in the diagnosis and treatment of psychiatric illnesses. Four quality improvement research projects involving the implementation of evidence-based practices for anxiety and depression [ 33 ], case management by nurses and self-management support for frequent users with chronic disease [ 34 ], chronic disease prevention and management services in primary care with primary care physician and nurse collaboration [ 35 ] and health equity for individuals living in poverty [ 36 ] had recently been carried out or were simultaneously underway.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed this literature and materials and found wide variability in the naming and description of skills. For example, where some authors suggested facilitators need communication skills [38,45], others suggested they need specific communication skills, e.g., good listening skills [21], presentation skills [46], or the ability to put arguments across [47].…”
Section: Discussionmentioning
confidence: 99%